Optimizing the Role of Health Unit Cadres in Early Breast Cancer Detection Education for Young Women - Ridlo, Muhamad; Hilfida, Nurullia Hanum (Jurnal Pengabdian West Science, 2026)
Breast cancers are among the leading causes of death in women; however, early detection behaviors among adolescents remain low. This community service program aimed to optimize the role of School Health Unit (UKS) cadres through a peer group education approach to enhance awareness of early cancer detection. The program was conducted at SMP IT Ustman Bin Affan Surabaya in October 2025, involving 25 UKS cadres. The methods included intensive training sessions, SADARI (Breast Self-Examination) simulations, and peer mentoring activities. The evaluation design employed pre-test and post-test. Results showed a significant increase in participants’ knowledge, with the average pre-test score rising from 52.16 to 85.72 in the post-test. This improvement confirms that empowering UKS cadres is effective in bridging the information gap regarding reproductive health among adolescents. The outcomes of this program include the formation of competent UKS cadres and the improvement of health literacy within the school environment
Keywords: Breast Cancer; Early Detection; Health Education; UKS Cadres; Peer Group Education.